THE CONTRIBUTION OF RELIGIOUS EDUCATION TO THE FORMATION OF TOLERANCE AWARENESS AMONG STUDENTS - Alhafiz Maulana; Anggi Armayani; Ayu Irma Ningtias; Chairuliah; Mirza Syadat Rambe; Nur Sella (Yayasan Amanah Nur Aman, 2026)
This study stems from crucial issues related to the degradation of social sensitivity and the escalation of intolerance among students, particularly in the context of social media penetration and increasingly complex interpersonal interactions. Religious education is abstracted as a fundamental means for internalizing values of moderation and character building that uphold diversity. The purpose of this study is to investigate the contribution of religious education in constructing tolerance awareness among students in the secondary school ecosystem. This study adopted a quantitative methodology with an explanatory survey design, involving 120 student respondents who were analyzed using a Likert scale questionnaire. The validity and reliability of the data were strengthened through classroom observations, interviews with educators, and a review of curriculum documentation. Descriptive evaluation revealed that the implementation of religious education was at a “good” level, while tolerance awareness among students was at a “high” level. The results of simple linear regression analysis indicate a significant statistical determination between the variables of religious education and tolerance awareness, as shown by a significance value of 0.001. Furthermore, the coefficient of determination of 0.42 underlines that 42% of the variability in tolerant attitudes can be explained by the quality of religious education implementation. The discussion of this study emphasizes that religious education that applies dialogical, reflective, and situational understanding-based methods effectively improves students' capacity to appreciate diversity and foster peaceful relationships. Furthermore, the example set by educators has proven to be a crucial factor in instilling values of tolerance in students. The essence of this study's findings concludes that religious education makes a substantial and crucial contribution to fostering awareness of tolerance in students. Therefore, its implementation requires continuous development with a moderate, humancentered, and inclusive approach to enrich social character in a culturally diverse educational ecosystem.